Anticancer activity of pyrithione zinc in oral cancer cells identified in small molecule screens and xenograft model: Implications for oral cancer therapy. Issue 8 (21st May 2015) - Srivastava, Gunjan; Matta, Ajay; Fu, Guodong; Somasundaram, Raj Thani; Datti, Alessandro; Walfish, Paul G.; Ralhan, Ranju
Abstract : Oral squamous cell carcinoma (OSCC) patients diagnosed in late stages have limited chemotherapeutic options, underscoring the great need for development of new anticancer agents for more effective disease management. We aimed to identify novel anticancer agents for OSCC using quantitative high throughput assays for screening six chemical libraries consisting of 5170 small molecule inhibitors. In depth characterization resulted in identification of pyrithione zinc (PYZ) as the most effective cytotoxic agent inhibiting cell proliferation and inducing apoptosis in OSCC cells in vitro. Further, treatment with PYZ reduced colony forming, migration and invasion potential of oral cancer cells in a dose‐dependent manner. PYZ treatment also led to altered expression of several key components of the major signaling pathways including PI3K/AKT/mTOR and WNT/β‐catenin in OSCC cells. In addition, treatment with PYZ also reduced expression of 14‐3‐3ζ, 14‐3‐3σ, cyclin D1, c‐Myc and pyruvate kinase M2 (PKM2), proteins identified in our earlier studies to be involved in development and progression of OSCCs. Importantly, PYZ treatment significantly reduced tumor xenograft volume in immunocompromised NOD/SCID/Crl mice without causing apparent toxicity to normal tissues. Taken together, we demonstrate in vitro and in vivo efficacy of PYZ in OSCC. In conclusion, we identified PYZ in HTS assays and demonstrated in vitro and in vivo pre‐clinical efficacy of PYZ as a novel anticancer therapeutic candidate in OSCC. Highlights: High throughput screening of chemical libraries identified pyrithione zinc (PYZ) as a potent anticancer agent for OSCC. PYZ inhibited cell proliferation and induced cell death. PYZ targeted PI3K/Akt/mTOR and Wnt/β‐catenin signaling in OSCC. PYZ treatment reduced tumor growth in vivo. Pre‐clinical efficacy of PYZ as a novel anticancer agent for OSCC was demonstrated.